A comparative analysis of operating performance: evidence from the top five pharmaceutical companies of Bangladesh listed with Dhaka stock exchange - Haque, Samina; Amin, Shabnaz (© 2013 European Journal of Economics, Finance and Administrative Sciences, 2016)
This article was published in European Journal of Economics, Finance and Administrative Sciences [© 2013 European Journal of Economics, Finance and Administrative Sciences] The article website is at: http://www.europeanjournalofeconomicsfinanceandadministrativesciences.com/issues/EJEFAS_58.html